Burnout, life satisfaction, and work-related quality of life among psychologists - Santana Ferreira, Silvia Morais de; Zaia, Victor (Frontiers in Psychology, 2025)
IntroductionThe Work-Related Quality of Life (WRQoL) is a complex, multidimensional concept, and its assessment is challenging due to a lack of consensus on the factors involved. While the WRQoL Scale has been validated in various countries, no translation into Brazilian Portuguese existed until this study. The primary aim was to validate the Brazilian Portuguese version of the WRQoL Scale, using psychologists as the target population, and to measure burnout and life satisfaction in this group.MethodsA backtranslation process was followed, involving bilingual translators and a focus group of psychology professionals to refine the final version. A total of 610 psychologists participated, completing the Maslach Burnout Inventory, the Life Satisfaction Scale, and the WRQoL Scale via an online platform (SurveyMonkey®). Exploratory and confirmatory factor analyses were conducted to test and refine the factor structure of the WRQoL Scale. Spearman's correlations and group comparison analyses were also performed.ResultsSeventy-six percentage of participants reported adequate life satisfaction, while 60.2% exhibited burnout symptoms, particularly in emotional exhaustion and depersonalization. Protective factors for the mental health of psychologists were identified. The final version of the WRQoL Scale included 23 items across three factors, with good internal consistency (Cronbach's alpha = 0.89 ICC = 0.96).DiscussionThe WRQoL Scale - Brazilian version, demonstrated adequate psychometric properties, as evidenced by its construct validity and internal consistency. This provides evidence that the WRQoL Scale is a adequate tool that can measure work-related quality of life in psychologists.